1991
DOI: 10.1007/bf01232825
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a human cDNA encoding amidophosphoribosyltransferase and functional complementation of a CHO Ade?A mutant deficient in this activity

Abstract: We report here the isolation of a human cDNA encoding the first step in de novo purine biosynthesis, amidophosphoribosyltransferase (PRAT). The human PRAT cDNA was isolated by complementation of a Saccharomyces cerevisiae ade4 mutant deficient in PRAT enzymatic activity. The identity of the isolated cDNA, designated pAdeA-3, was confirmed by several independent methods. Genomic DNA sequences homologous to pAdeA-3 show coordinate segregation with the hypoxanthine nutritional requirement in Chinese hamster ovary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…1). A number of chicken pur genes have been isolated by suppression of E. coli pur mutations (Chen et al, 1990), whereas human and Drosophila pur cDNAs have been cloned by suppression of yeast ade mutations (Henikoff et al, 1981;Schild et al, 1990;Barton et al, 1991). In plants, suppression of E. coli mutant phenotypes has been used successfully to isolate the phosphoenolpyruvate carboxylase cDNAs from a maize library (Izui et al, 1986) and a superoxide dismutase cDNAs from Arabidopsis and tobacco libraries (Van Camp et al, 1990).…”
Section: Air Synthetase Cene Phylogenymentioning
confidence: 99%
“…1). A number of chicken pur genes have been isolated by suppression of E. coli pur mutations (Chen et al, 1990), whereas human and Drosophila pur cDNAs have been cloned by suppression of yeast ade mutations (Henikoff et al, 1981;Schild et al, 1990;Barton et al, 1991). In plants, suppression of E. coli mutant phenotypes has been used successfully to isolate the phosphoenolpyruvate carboxylase cDNAs from a maize library (Izui et al, 1986) and a superoxide dismutase cDNAs from Arabidopsis and tobacco libraries (Van Camp et al, 1990).…”
Section: Air Synthetase Cene Phylogenymentioning
confidence: 99%
“…The purine nucleotides IMP, AMP and GMP induce formation of an inactive tetramer (224 kDa) of amidophosphoribosyltransferase from an active dimer (112 kDa) found in the presence of P-Rib-PP [22,28], Using sucrose density centrifugation, we showed that piritrexim 7.2 s) from the active dimer (6.7 s) as shown in …”
Section: Methodsmentioning
confidence: 71%
“…A gene involved in de novo purine biosynthesis, PA1CS (phosphoribosylaminoimidazole carboxylase (EC 4.1.1.21)) has been newly cloned (Schild et al, 1990) and mapped to 4pl6.3-4q21 using somatic cell hybrids, (Barton et al, 1991a). It joins a previously mapped and more recently cloned (Barton et al, 1991b) member of this enzyme pathway (PPAT) on chromosome 4. The eucaryotic initiation factor 4E (EIF4EL1) has been mapped to4pl5-4qter using somatic cell hybrids (Pelletier et al, 1991).…”
Section: New Genesmentioning
confidence: 99%